2023
DOI: 10.1002/gch2.202300011
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Storage Tanker Lifetime Assessment

Abstract: CO 2 capture and storage (CCS) is an important strategy to reduce global CO 2 emissions. This work presents both cutting-edge carbon storage tanker design, as well as novel reliability method making possible to extract useful information about the lifespan distribution of carbon capture systems from their recorded time history. The method outlined may be applied on more complex sustainable systems that are exposed to environmental stresses throughout the whole period of their planned service life. The latter i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 22 publications
(4 citation statements)
references
References 34 publications
(61 reference statements)
0
4
0
Order By: Relevance
“…Then, the estimate from the Gaidai‐Xing approach was compared to the level of the probability p0.33em=103.50.33em$p\ = {10}^{ - 3.5}\ $, associated with this contour line. It was observed that the estimating results of the probability level by ACER2D was within the 95% Confidence Interval (CI) estimated by Gaidai‐Xing 26,64–70 …”
Section: Resultsmentioning
confidence: 52%
“…Then, the estimate from the Gaidai‐Xing approach was compared to the level of the probability p0.33em=103.50.33em$p\ = {10}^{ - 3.5}\ $, associated with this contour line. It was observed that the estimating results of the probability level by ACER2D was within the 95% Confidence Interval (CI) estimated by Gaidai‐Xing 26,64–70 …”
Section: Resultsmentioning
confidence: 52%
“…Note that P ≡ P(1) is from Equation (1). Non-exceedance system survival probability P(λ) may be now estimated as follows [54][55][56][57][58][59][60][61][62][63][64]:…”
Section: Novel Reliability Methodsmentioning
confidence: 99%
“…. being ranked based on the non-decreasing occurrence times of these local maxima [59][60][61][62][63][64][65]. Figure 5 presents an example of a non-dimensional assembled vector → R, consisting of assembled local maxima of the FWT's internal forces; λ > 0.05 cut-on limit was used for illustrative purposes, as lower values λ ≥ 0 are obviously irrelevant for the failure/hazard system's PDF tail extrapolation towards the target λ = 1.…”
Section: Failure Probability Estimationmentioning
confidence: 99%
“…Figure 3b presents return periods expressed in 2, 5, and 10 years, respectively, per 2D contour line. Return periods of the order of 10 years are of practical relevance for GPEH design (Daqaq, 2015; Fazeres‐Ferradosa, Taveira‐Pinto, Romão, et al., 2018; Rugbjerg et al., 2006; Sun, Gaidai, Wang, et al., 2023) as well as for various offshore wind energy installations, such as floating wind turbines (see Sun, Gaidai, Wang, et al., 2023), wind farm offshore vessels, joint wave heights, and wind speed 2D bivariate statistics (Avvari et al., 2017; Daue & Kunzmann, 2008; Gaidai et al., 2019; Gaidai et al., 2020; Gaidai, Hu, et al., 2023; Gaidai, Wang, & Yakimov, 2023; Gaidai, Wang, Wu, et al., 2022; Sherrit et al., 2014; Soma & De Pasquale, 2013; Stanton et al., 2012; Williams et al., 2004; Xing et al., 2022).…”
Section: Bivariate Statisticsmentioning
confidence: 99%